Skeletal Muscle Mass Loss During Cancer Treatment: Differences by Race and Cancer Site. - Min Kyeong Jang; Chang Gi Park; Susan Hong; Laddu, Deepika; Hongjin Li; Rhee, Esther; Doorenbos, Ardith Z. (Oncology Nursing Forum, 2020)
OBJECTIVES: To examine skeletal muscle mass change in a racially diverse sample of patients undergoing cancer treatment, determine significant predictors of muscle mass loss, and explore the interaction of race and cancer site. SAMPLE & SETTING: A retrospective analysis was conducted for 212 patients seeking treatment at a university hospital clinic. METHODS & VARIABLES: Skeletal muscle mass index (SMI) was determined by computed tomography at the time of cancer diagnosis and with cancer treatment. RESULTS: One hundred thirty-four patients (63%) had SMI loss with cancer treatment. Race and cancer site were found to be significant predictors of SMI loss. Compared to other racial groups, non-Hispanic Black (NHB) patients had the greatest SMI loss (p < 0.001) with cancer treatment. NHB patients with rectal cancer experienced the greatest SMI loss compared to patients of other races and cancer types. IMPLICATIONS FOR NURSING: To improve survivorship care for patients with cancer, it is essential to develop strategies for assessing and managing skeletal muscle mass loss throughout treatment, particularly for NHB patients with rectal cancer.